Impaired decision-making in borderline personality disorder - Bajzát, Bettina; Soltész, Péter; Soltész-Várhelyi, Klára; Lévay, Evelyn Erika; Unoka, Zsolt Szabolcs (Frontiers in Psychology, 2023)
Borderline personality disorder (BPD) is a complex mental disorder with core symptoms like interpersonal instability, emotion dysregulation, self-harm, and impulsive decision-making. Previous neuropsychological studies have found impairment in the decision-making of patients with BPD related to impulsivity. In our study, we focus on a better, more nuanced understanding of impulsive decision-making in BPD with the help of Rogers' decision-making test that simulates a gambling situation. A novelty of our study is that we excluded from further analysis non-compliant participants based on their performance. Outlier participants on the measures proportion of good choices and average of wager choice number were filtered out to represent the population that understood the basic premise of the task and showed minimal motivation to gain rewards. Thus participants often choosing the less likely color or frequently choosing the first bet amount available (to probably speed up the test) were omitted from further analysis. Another novelty is that we assessed and reported six variables that examine Deliberation Time, Quality of Decision, Risk-taking, Overall proportion bet, Delay aversion, and Risk adjustment. Forty-three women with BPD participated in the study, and 16 non-compliant were excluded. As for the healthy control group, 42 women participated in the study, and four non-compliant were excluded. Thus, we compared the data of 27 patients with BPD with 38 healthy controls. Our results show that there are significant differences amongst the groups regarding the Quality of Decision Making (F(1,63)=5.801, p=.019) and Risk Adjustment (F(1,63)=6.522, p=.013). We also found significant interactions between group and winning probability regarding Risk Taking (F(4,252) = 4.765 p = .001) and Overall proportion of bets, i.e., the average proportion of bets relative to the total score of the subject (F(4,252)=4.505, p=.002). Our results show that the two groups use different decision-making strategies that can have various associations with everyday life situations.